PEMBUATAN ADSORBEN DARI CANGKANG KERANG BULU YANG DIAKTIVASI SECARA TERMAL SEBAGAI PENGADSORPSI FENOL - Jeffry Haryadi Nasution, Iriany (Universitas Sumatera Utara, 2015)
Fur shells adsorbent can be used to adsorp phenol. Adsorption capability of the adsorbent can be enchanced by thermally activation process. The purpose of this research is to study the effect of activation temperature on the characteristics of fur shells adsorbent. Materials that used in this research are fur shells and phenol solution. Observed variables are surface area of adsorbent, density of adsorbent, moisture and fly ash content of adsorbent, and residual concentration of phenol. The research is started by heating fur shells at temperature 1100C, 5000C and 8000C in a furnace. The adsorbents obtained are characterized by using BET metode. The adsorption capability of adsorbents are analized by phenol solution. The residual concentration of phenol is measured with Spectrophotometer UV-Vis. The results show that surface area of adsorbent, moisture and fly ash content have fulfilled National Standard of Indonesia (SNI). The phenol adsorption behaviour follows Langmuir Isoterm.